KONVERGENSI SIMBOLIK SEBAGAI BASIS INTEGRASI SOSIAL KOMUNITAS HINDU-BALI DI DAERAH TRANSMIGRASI - I Wayan Astraguna; I Nengah Alit Nuriawan; Komang Reza Kartika (Institut Agama Hindu Negeri Gde Pudja Mataram, 2026)
This research is based on the social reality of the Balinese Hindu community in the transmigration area of ​​East Luwu Regency, which, despite its diverse internal backgrounds, is able to build relatively harmonious social relations. Previous studies have primarily viewed integration as a result of structural adaptation or intercultural interaction, while the dimension of shared meaning-making in group communication has received less attention. Therefore, this research aims to examine the process of symbolic convergence in group communication and its relationship to the formation of social integration. The approach used was qualitative with a communication ethnography design. Data were obtained through participant observation, in-depth interviews, and documentation of purposively selected community members. Analysis was conducted in stages, exploring fantasy themes, key symbols, collective narratives, and social cohesion as manifestations of symbolic convergence. The findings indicate that symbolic convergence develops through four stages: the emergence of fantasy themes based on shared experiences, the use of symbols to unify meaning, the formation of collective narratives, and the emergence of social cohesion. This confirms that social integration is the result of an ongoing communicative process. This study strengthens the relevance of symbolic convergence theory in the local context and emphasizes the importance of group communication spaces in building social harmony.